2010
DOI: 10.1038/ng.562
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies variants at CSF1, OPTN and TNFRSF11A as genetic risk factors for Paget's disease of bone

Abstract: Paget’s disease of bone (PDB) is a common disorder with a strong genetic component characterised by focal increases in bone turnover which in some cases is caused by SQSTM1 mutations. To identify additional susceptibility genes we performed a genome wide association study in 750 PDB cases without SQSTM1 mutations and 1002 controls and identified three candidate loci for the disease which were replicated in an independent set of 500 cases and 535 controls. The strongest signal was with rs484959 on 1p13 close to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
217
3
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 261 publications
(233 citation statements)
references
References 43 publications
11
217
3
2
Order By: Relevance
“…Three SNPs (rs1561570, rs825411, and rs2095388), all located within a 30-kb region, were analyzed in both stages of the study, and the strongest signal was observed for SNP rs1561570. (20) These findings were replicated in a larger cohort of PDB patients from different countries. (21) OPTN, a candidate gene located in this region, negatively regulates TNFa-induced NF-kB activation, and a putative NF-kB binding site has been identified in the OPTN promoter.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…Three SNPs (rs1561570, rs825411, and rs2095388), all located within a 30-kb region, were analyzed in both stages of the study, and the strongest signal was observed for SNP rs1561570. (20) These findings were replicated in a larger cohort of PDB patients from different countries. (21) OPTN, a candidate gene located in this region, negatively regulates TNFa-induced NF-kB activation, and a putative NF-kB binding site has been identified in the OPTN promoter.…”
Section: Discussionmentioning
confidence: 66%
“…Conversely, nonparametric analyses revealed most suggestive linkage on chromosomes 10 (Zmax ¼ 6,2 at 20 to 30 Mbp from 10pter) and 8 (Zmax ¼ 6,2 at 120 Mb). Given the consistency of the former association with some previous studies in SQSTM1-negative patients, (19)(20)(21) we performed a genetic screening of the OPTN and CSF1 gene loci (see above), but we failed to identify any causative mutation at both the genomic and transcription levels.…”
Section: Genetic Analysismentioning
confidence: 67%
See 3 more Smart Citations